1992
DOI: 10.1620/tjem.168.539
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Pylorus-Preserving Gastrectomy for Gastric Ulcer.

Abstract: The postoperative results of pylorus-preserving gastrectomy (PPG) for gastric ulcer performed in 134 patients during the past 25 years (mean postoperative period, 16.6 years) were studied. The incidence of postoperative complications was low. Dumping syndrome occurred in only 4.4% and 0% of cases as assessed by questionnaire and interview, respectively. Four (5.4%) of 74 patients available for this study had ulcer recurrence. In one of these four patients concurrent gastroduodenal ulcer was suspected from preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Prior studies [13][14][15], suggested that LAPPG would provide better QOL than LADG. Tomita et al [14] and others [23,24] report that pylorus-preserving gastrectomy (PPG) alleviates postoperative gastrointestinal symptoms, such as appetite loss, reflux esophagitis, early dumping syndrome, lost body weight, endoscopic reflux esophagitis, endoscopic gastritis in the remnant stomach, and postgastrectomy cholecystolithiasis, better than conventional distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies [13][14][15], suggested that LAPPG would provide better QOL than LADG. Tomita et al [14] and others [23,24] report that pylorus-preserving gastrectomy (PPG) alleviates postoperative gastrointestinal symptoms, such as appetite loss, reflux esophagitis, early dumping syndrome, lost body weight, endoscopic reflux esophagitis, endoscopic gastritis in the remnant stomach, and postgastrectomy cholecystolithiasis, better than conventional distal gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach offers several advantages associated with preserving the pyloric function, such as the prevention of dumping syndrome [13], protection against bile mucosal injury of the remnant stomach [14], and less postoperative body weight loss [15]. However, LAPPG is not as widely performed as LADG, and there has been no reported comparison between non-pylorus-preserving gastrectomy and pylorus-preserving gastrectomy in settings where laparoscopic techniques are applied to the surgery, other than the report of Urishihara et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…We note that Sawai et al 3 reported a surgical technique to preserve the pylorus during distal gastrectomy with radical lymph node dissection. Although the operation described by Sawai et al 4 is not a limited operation, the postoperative function is better than that after common operations without pylorus preservation. 4 In this study, we examine the results of SR for treatment of EGC of the middle stomach, compared with the results of DR, in terms of surgical risk, postoperative organ function, and survival rates.…”
mentioning
confidence: 86%
“…Although the operation described by Sawai et al 4 is not a limited operation, the postoperative function is better than that after common operations without pylorus preservation. 4 In this study, we examine the results of SR for treatment of EGC of the middle stomach, compared with the results of DR, in terms of surgical risk, postoperative organ function, and survival rates. We also compare the results of limited lymphadenectomy of D0 -1 with the results of common dissection of D2.…”
mentioning
confidence: 86%
“…10 Maki's colleagues summarized the long-term results of PPG in 1992. 11 A report on the outcomes of 134 patients followed up over 25 years revealed peptic ulcer recurrence in 5.4% and dumping syndrome in only 4.4% and 0% as determined by questionnaire and interview, respectively.…”
Section: For Gastric Ulcersmentioning
confidence: 99%